INFLUENCE OF CUSTOMER SERVICE AND VALUE TO CUSTOMER SATISFACTION PDAM TIRTA MOEDAL SEMARANG - Tambunan, Linggom; Waluyo, Handoyo Djoko; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Pdam Tirta Moedal semarang is a local drinking water companies that move in the fields clean water sales. As a company supplier of clean water, in addition to the local revenue, the supply of water taps Tirta Moedal Semarang also aims to meet the needs of the community will clean water, used for household needs, office,Â building government building, the school, places of worship and other business purposes. Research aims to understand the value of the influence of customer service and customer satisfaction PDAM Tirta Moedal Semarang. Type research that is used is namely eksplanatory research to the population of active customers PDAM Tirta Moedal Semarang. Sample the ones involved are as many as 100 people the sample collection by applying a technique uses the method purposive (engineering the determination of the sampling method of sample) done with certain consideration. Engineering data collection in the research by using interviews and questionnaires. The results of research we can conclude that partial evaluation for such variables here influential significantly to customer satisfaction. The service for satisfaction pelaanggan where t count as much as 8,817 > t table (1,9845). The value of customer customer satisfaction where the value of t count 5,126 > t table (1,9845). Simultaneously all the variables influential significantly to customer satisfaction with the results of the count ( 40,119 ) > f table ( 3,089 ). Advice that can be given in research this is a company need to increase service quality in terms of technical and non company technical, so that the customers that appears good will and the customer will be satisfied.